Analysis of Digital Legal Acceptance based on the Technology Acceptance Model 3 (TAM3) - Siti Nur Azizah; Hermin Endratno; Harjono Harjono (Universitas Muhammadiyah Purwokerto, 2022)
This study aims to analyze the acceptance of the PeduliLindungi application from a public perspective using the Technology Acceptance Model (TAM) concept. The government requires the PeduliLindung application to track community activities through the Decree of the Minister of Communication and Informatics No. 171 of 2020. The Indonesian government hopes that this application records the mobility of infected patients and becomes a solution to reduce the transmission of COVID-19. However, PeduliLindungi is a new application that developed after the pandemic. Thus, the user acceptance of this app is questionable. This is a survey analysis from 102 respondents using Structural Equation Model-PLS. The results found that perceived usefulness, system failure, and social influences affect the user intent of the PeduliLindungi app while perceived ease of use is not. This app was applicable to record individual movement as virus prevention in the future. This is a contribution to theory and practice in economics and business. In theory, this research provides a new and more comprehensive view of fundamental human behaviour idea. In practice, this research is able to measure the effectiveness of government regulations in responding to an unexpected global crisisKeywords: Behavioral Intention, Technology Acceptance Model, PeduliLindungi App